PREVALENSI DAN FAKTOR - FAKTOR YANG TERKAIT DENGAN PERKEMBANGAN KEJADIAN PENYAKIT TUBERKULOSIS MULTIDRUG RESISTANT DI KOTA MEDAN - RIFQY IMSYA AL AYYUBI LUBIS; HUMAIRAH MEDINA LIZA LUBIS (JURNAL ILMIAH MAKSITEK, 2021)
Multidrugs resistant tuberculosis is a type of TB bacterial resistance to at least two first-line anti-TB drugs, namely Isoniazidand Rifampin which are the two most effective TB drugs.1 A global total of 186,772 cases of MDR / RR-TB were detectedand known in 2018, up from 160,684 in 2017, 156,071 cases were registered in treatment, up from 139,140 in 2017. Theestimated incidence of drug-resistant TB cases in Indonesia was 24,000 in 2018, but in 2018 only 9180 TB RR patients werefound and only 49% of TB patients were confirmed. RR initiating second-line TB treatment. The aim of this study was tocollect data on the prevalence and factors associated with the development of the incidence of multidrug resistanttuberculosis in the city of Medan. This study was a descriptive analytic study with a cross section design. The researchsample consisted of 28 MDR TB patients at Puskesmas Helvetia and RSUD Pirngadi Medan, which were taken by totalsampling method. This study was tested with the Pearson correlation test. The results of this study showed that the riskfactors for the sample of this study were male gender 15 people (53.6%), mean age above 40 years 21 people (75.0%) 26people (92.9%) married status, 25 people with high school education level (89.3%), 9 self-employed people (32.1%), monthlyincome less than 1,000,000 15 people (53.6%), history of use Previous OAT OAT line 1 (complete) 11 people (39.3%), ahistory of smoking 14 people (50.0%), a history of not consuming alcohol 23 people (82.1%), patient knowledge about MDRTB was less or bad 18 people (53.6%), patient compliance in taking medicine was good 17 people (60.7%), 16 people wereless motivated to take medication (57.1%) and the patient's daily habits were good 14 people (50.0%). The relationshipbetween several risk factors such as previous drug use history with the level of patient adherence to MDR TB, the level ofmedication adherence and motivation to take medication and vice versa. meanwhile, daily habits such as smoking andalcohol consumption had no relationship with previous history of drug use, patient adherence to MDR TB, level of medicationadherence and motivation to take medication.